Surgery for wilms’ tumor, Does Preoperative Chemotherapy Ease its Surgical Procedure? - Farhan, Saad D. (Journal of the Faculty of Medicine Baghdad, 2013)
Background: The optimal timing of surgery for Wilms’ tumor has been debated for many years. It appears dubious whether surgical ease or per operative complications consistently improved after preoperative chemotherapy. Materials and Methods: This is a cross section study ,the sample collected from January 2009 to November 2012 .Thirty four patients were selected after informed consent . Patients aged between 10 months and 5 years who were newly diagnosed with Wilms’ tumors. including (17) patients with unilateral wilms tumors received immediate nephrectomy without preoperative chemotherapy according to the National Wilms’ Tumor Study Group protocol and (16) patients with unilateral Wilms’ tumors and one patient with bilateral wilms tumor received delayed nephrectomy or partial nephrectomy following preoperative chemotherapy according to the International Society of Pediatric Oncology( SIOP) WILMS TUMOR 2001/UK Final Version /January 2002 protocol.Objective : To compare the use of immediate nephrectomy versus delayed nephrectomy or partial nephrectomy following neo adjuvant chemotherapy for treatment of non metastatic Wilms’ tumor, in terms of surgical morbidity and per operative complications . Results: there is significant change in the maximal tumor size (more than 50% reduction in the maximal tumor diameter) was observed in 52.9% of patients receiving pre operative chemotherapy. There is reduction in the complication rate in that patient receiving pre operative chemotherapy. These observed specifically for decreasing residual tumor and tumor spillage episodes. Bilateral partial nephrectomy after neo adjuvant chemotherapy was done for one patient (5.6%) with bilateral wilms tumor. We found significant decrease in the complication rate mainly for those patients with high risk score receiving pre operative chemotherapy rather than those with low risk score. Conclusion: We would favor tumor resection when it is possible as early in therapy as is practical and safe, when there is concern about the safety of primary tumor resection the pre operative chemotherapy can be safely initiated.